2015
DOI: 10.31018/jans.v7i2.698
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability analysis for various yield and quality traits in rice (Oryza sativa L.)

Abstract: An investigation was undertaken to assess the combining ability for yield and quality traits in rice. Three WA cytoplasmic male sterile lines of rice i.e., IR-58025A, IR-68897A and Pusa 6A were crossed with six restorer genotypes i.e., Sanwal Basmati, Pusa Sugandh-2, Pusa Sugandh-3, Pusa Sugandh-5, Pusa 2517-2-51-1 and HUR-JM-59221 in line x tester design to generate 18 hybrids. Among the female parents, IR-58025A revealed significant desirable value of GCA effect for yield per plant and most of the quality tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
4
5
0
Order By: Relevance
“…The contribution of maternal and paternal interaction (line x tester) was more important for grain yield/plant (62.53%). These results are agreed with the results obtained by Waza et al, (2015) and Rahaman (2016) they found the contribution of maternal and paternal interaction (line x tester) was more important for grain yield/plant.…”
Section: Resultssupporting
confidence: 93%
“…The contribution of maternal and paternal interaction (line x tester) was more important for grain yield/plant (62.53%). These results are agreed with the results obtained by Waza et al, (2015) and Rahaman (2016) they found the contribution of maternal and paternal interaction (line x tester) was more important for grain yield/plant.…”
Section: Resultssupporting
confidence: 93%
“…Combining ability variances in the present study (Table 2) revealed that magnitude of additive genetic variance (ϭ 2 A) was higher than dominance variance (ϭ 2 D) for the characters days to 50% flowering, effective tillers, flag leaf width, kernel length after cooking, kernel width after cooking and volume expansion ratio indicating predominance of additive gene action. Similar views were expressed by Srinivas et al (2015) and Rukmini Devi et al (2017) for kernel length after cooking and kernel width after cooking, Salgotra et al (2009) and Showkat et al (2015) for days to 50 % flowering and Asvin Kirubha et al(2019) hulling percent, milling percent, head rice recovery, kernel length, kernel width, length/breadth ratio, kernel elongation ratio, alkali spreading value and water uptake, the value of ϭ 2 A is lower than ϭ 2 D indicating the predominance of non additive gene action. The presence of non additive genetic variance offer scope for exploitation of heterosis.…”
Section: Resultssupporting
confidence: 80%
“…The contribution of paternal and maternal interaction (female x male) was observed to be best in proportion for the traits effective tillers, filled seeds /panicle, yield/plant, hulling percent, milling percent, head rice recovery, kernel width after cooking, kernel elongation ratio and water uptake indicating that these characters are influenced by non additive gene action. The high contribution of maternal and paternal interaction in rice for the traits yield/plant, effective tillers, head rice recovery, kernel width after cooking also reported by Showkat et al (2015). Combining ability variances in the present study (Table 2) revealed that magnitude of additive genetic variance (ϭ 2 A) was higher than dominance variance (ϭ 2 D) for the characters days to 50% flowering, effective tillers, flag leaf width, kernel length after cooking, kernel width after cooking and volume expansion ratio indicating predominance of additive gene action.…”
Section: Resultsmentioning
confidence: 53%
“…Dominant gene action seems to be more important for the expression of physico-chemical traits like head rice recovery, kernel length, length / breadth ratio, linear elongation ratio, volume expansion ratio, alkali spreading value, gel consistency and amylose content which was in agreement with the findings of Adilakshmi and Upendra (2014) and Thakare et al (2013). Milling percent also had higher SCA variance as reported by Waza et al (2015) whereas Alkali spreading value was the single character which exhibited additive genetic variance in contrast to their reports.…”
Section: Resultsmentioning
confidence: 50%
“…,Waza et al (2015), Ghosh et al(2013),Srivastava et al (2012), Saidaiah (2010) and Jayasudha and Sharma…”
mentioning
confidence: 99%